Case studies to illustrate the rotorcraft certification by simulation process; CS 29/27 category A rejected take-off, confined area - White, Mark D.; Dadswell, Christopher; Padfield, Gareth D.; van’t Hoff, Stefan; Bakker, Richard; Lu, Linghai; Quaranta, Giuseppe; Podzus, Philipp (German Society for Aeronautics and Astronautics (DGLR: Deutsche Gesellschaft für Luft- und Raumfahrt), 2023)
This paper is one of a set presented at the 49th European Rotorcraft Forum discussing results from the EU Clean Sky 2 project, Rotorcraft Certification by Simulation (RoCS). The process developed by the RoCS team provides guidance on the use of flight simulation in certification and features four case studies that illustrate aspects of the process applied using flight simulation models and flight test data provided by Leonardo Helicopters. This paper presents the case study for Rejected Take-Off (RTO): Category A in a Confined Area, for the relevant certification paragraphs in the EASA Certification Specifications CS-27 and CS-29. The relevant paragraphs from the Specifications are described and results from simulation model fidelity assessment, and updating compared with test data, are presented for a reference flight condition. Results from piloted simulation trials, with a ‘new’ Flight Test Manoeuvre (FTM), are included to illustrate flight simulator fidelity assessment methods and to illustrate how the Rotorcraft Certification by Simulation process can be achieved.
© The Authors